Geological modeling of carbonate fracture-cavity reservoir: case study of Shunbei fault zone No. 5 - Li, Bolin; He, Yunfeng; Chen, Wen; Shang, Haojie; Wang, Lixin (Frontiers in Earth Science, 2025)
In the Shunbei area of the Tarim Basin, China, carbonate fault-controlled fracture-cavity reservoirs exhibit complex internal structures and complex heterogeneity, with primary reservoir spaces including fault plane, cave-like, and disordered body reservoirs. Traditional geological modeling methods, such as multipoint geostatistical stochastic simulations or threshold-truncated modeling based on single seismic attribute volumes, are not adequate for effectively characterizing the complex spatial distribution of fault plane, cave-like, disordered body reservoirs, and their internal grille structures. This limitation leads to insufficient accuracy in inter-well connectivity predictions and constrains efficient hydrocarbon development. This study proposes a novel trendline-constrained object-based modeling approach, taking the Shunbei No. 5 strike-slip fault zone as a case study. First, deterministic modeling methods were employed to establish fault-controlled body contour models through seismic attribute fusion (structure tensor, energy gradient, and variance attributes) calibrated with well-log data. For internal architecture characterization, a hierarchical modeling strategy was implemented. The methodology innovatively integrates principal stress orientation trendline tracking algorithms with cumulative probability sampling techniques, achieving quantitative modeling of alternating grille structures composed of crush belt (breccia belt and fracture belt) and bedrock belt. Results show that this method accurately maps the spatial distribution of fault plane and cave-like reservoirs, ensuring reserve estimation errors and numerical simulation discrepancies are both kept below 10%. The proposed trendline-constrained object-based modeling method overcomes the limitations of conventional techniques in precisely characterizing grille morphologies, enabling refined 3D characterization of fault-controlled fracture-cavity reservoirs. This research provides crucial technical support for the development of carbonate hydrocarbon reservoirs.